Wątki angelologiczne w egzegezie patrystycznej 1Kor 11,10 - Paczkowski, Mieczysław (Vox Patrum, 2023)
Relatively 1 Cor 11:10 received the most attention from those of the early Church writers who dealt more extensively with the „woman’s question”. The question of the veil for women was analyzed in the social, religious and cultural contexts of antiquity. St. Paul's text encouraged Christians to seek stricte religious arguments to justify the practice of wearing the veil by women, placing it in the context of a theological choice. Ancient Christian writings confirm this view, but many authors choose the path of reflection impregnated with elements of angelological doctrine. However, there was no shortage of other interpretative contexts. In the ante-Nicene Fathers, it was possible to discover the hermeneutical links of the Pauline text with Gen 6:1-4. The range of „angels” referred to in the Pauline pericope was quite broad. They were identified not only with celestial beings but also with the fallen angels, the celebrants in the liturgy and its participants. It could also have been the strangers who observed the rites. In the later period, the issues were different. In reality, the doctrine of the Church and the social reasons, customs, as well as practices in liturgical assemblies have been consolidated. The veil became a symbol that invoked a positive image of women. The imposition of the veil (velatio) became synonymous with the consecration to God by the virgins.